Formalization of Methods in Criminalistics - L. P. Grynko (Law and Safety)
Scientific works on formalization of methods in criminalistics have been analyzed in the article. Despite the importance and relevance of these issues, it has been established that there is a number of unresolved issues in the theory of forensic science, as well as in investigative and judicial practice regarding the possibilities of formalizing methods and their implementation, which require separate independent research and in-depth reflection. Accordingly, the purpose of this article is to clarify the methods used to detect and investigate crimes and the possibilities of their formalization in criminalistics.